Innovations in Practice: Adapting a specialized ADHD parenting programme for use with 'hard to reach' and 'difficult to treat' preschool children. Issue 3 (22nd July 2014) - McEwan, Fiona; Thompson, Margaret; Laver‐Bradbury, Cathy; Jefferson, Harriet; Koerting, Johanna; Smith, Elizabeth; Knowles, Mark; McCann, Donna; Daley, David; Barton, Jo; Latter, Sue; Elsey, Helen; et al.
<x xml:space="preserve">Abstract</x> Background Effective implementation of parent training programmes for preschool Attention‐Deficit/Hyperactivity Disorder type is constrained by barriers limiting take‐up and effective engagement by 'hard to reach' and 'difficult to treat' families. Method We describe an evidence‐driven adaptation and piloting of an existing empirically supported preschool ADHD parenting programme to address these problems. Results The New Forest Parenting programme was changed substantially in terms of length; content and delivery on the basis of information gathered from the literature, from parents and practitioners, further modifications were made after the pilot study. Conclusions The adapted‐NFPP is currently being assessed for efficacy in a large multicentre randomized controlled trial.